C-MAC D-Blade video laryngoscope for awake double lumen tube placement: A case report. (February 2018) - Mittal, A.K.; Goel, N.; Dubey, J.
Abstract: Awake intubation for double lumen tube placement is a challenging task even for experienced clinicians, for smooth intubation different techniques and equipment are always desired. We report the successful use of C-MAC videolayrngoscope as a tool for awake intubation and double lumen tube placement.